2003
DOI: 10.1002/cncr.11408
|View full text |Cite
|
Sign up to set email alerts
|

Nausea and emesis remain significant problems of chemotherapy despite prophylaxis with 5‐hydroxytryptamine‐3 antiemetics

Abstract: BACKGROUNDClinical reports suggest that nausea remains a side effect of chemotherapy despite widespread use of serotonin receptor antagonists. This study summarized the frequency, timing, and intensity of postchemotherapy nausea for patients receiving doxorubicin, cisplatin, or carboplatin.METHODSThree hundred sixty chemotherapy‐naïve patients (73% female) were enrolled in a study testing the ability of an information intervention to reduce nausea. Of these, 322 subjects completed the Morrow Assessment of Naus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 183 publications
(62 citation statements)
references
References 12 publications
(8 reference statements)
0
62
0
Order By: Relevance
“…In various surveys in the U.S. 9 and Europe, 5,10 an incidence rate of 25-38% for delayed emesis and 55-60% for delayed nausea has been observed. Of greater note is the observation of an incidence rate of 18 -30% for delayed emesis and 23-36% for delayed nausea, even in the absence of acute nausea and emesis.…”
Section: Discussionmentioning
confidence: 98%
“…In various surveys in the U.S. 9 and Europe, 5,10 an incidence rate of 25-38% for delayed emesis and 55-60% for delayed nausea has been observed. Of greater note is the observation of an incidence rate of 18 -30% for delayed emesis and 23-36% for delayed nausea, even in the absence of acute nausea and emesis.…”
Section: Discussionmentioning
confidence: 98%
“…chemotherapy that contained either carboplatin, cisplatin, or doxorubicin and showed that 76% of patients developed some nausea during the first 5 days of receiving their chemotherapy. 16 No details were provided in that report regarding the antiemetic regimen(s) employed after Day 1 of chemotherapy. A second study focused primarily on moderately emetogenic chemotherapy and documented acute nausea in Ͼ 30% of patients and acute emesis in Ն 12% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of antiemetic control rates that combine dissimilar emetogenic regimens together to report overall success rates may not be a valid means of describing actual rates of nausea and emesis control in clinical practice. 10,16,17 This heterogeneity in antiemetic response among different chemotherapy regimens indicates the need for quality improvements and may guide clinicians to focus research on chemotherapy regimens for which antiemetic therapy is inadequate. Potential future studies that can be derived from this research include targeting certain chemotherapy regimens to test newer antiemetic agents (e.g., aprepitant) in children, redefining and/or combining the acute and delayed phases for antiemetic studies in children who receive chemotherapy, and conducting studies to examine markers of chemotherapy-induced nausea and emesis that may predict the heterogeneity in response for children of different ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2) In the late 1990s, several professional organizations such as the Multinational Association of Supportive Care in Cancer, the National Comprehensive Cancer Network, and the American Society of Clinical Oncology, convened antiemetic guideline groups and published theˆndings of these expert panels. 3 7) Each of these documents was based on analyses of the available published trials and provided nearly identical recommendations.…”
Section: Introductionmentioning
confidence: 99%